Integration of Local Values and Digital Technology in Empowering Tourism Village Communities in Bone Regency, South Sulawesi - Indrawati, Ajeng R; Asrijal, Andi; Zulkifli, Zulkifli; Hasnawati, Hasnawati; Erdawati, Mega (PT. Anagata Sembagi Education, 2025)
This study examines the integration of local wisdom values with digital technology in empowering tourist village communities in Bone Regency, South Sulawesi. Bone Regency has strong cultural values such as siri' na pacce which are the foundation of collective identity, but tourism village development policies are still uniform and do not accommodate local cultural characteristics. This study uses a descriptive qualitative approach with data collection through interviews, participatory observation, and documentation in several tourist villages. Thematic analysis was conducted to understand the dynamics of the meaning of local values, technology adaptation, and community participation. The results of the study indicate tension between cultural preservation and the demands of modern digitalization. Village communities adopt technology selectively with the important role of traditional leaders as curators of cultural content. Social media is an effective means of promoting and expressing cultural identity, but low digital access and literacy are obstacles. The study emphasizes the need for an inclusive and participatory digital empowerment approach, involving all community actors to make technology an instrument for preserving and strengthening culture while encouraging sustainable socio-economic transformation of tourist villages. This model is expected to bridge tradition and modernity harmoniously in the context of local tourism development.